Technology Blueprint Smart Fish Pond Monitoring and Inspection Device / Wan Nur Afifah Wan Anwar - Wan Anwar, Wan Nur Afifah (2020)
Smart fish pond monitoring and inspection device is a supplier company which distribute a very handful, useful and affordable product. It produces an easy-to-use device which helps life to get easier named as smart fish pond monitoring and inspection device. It allowed people to make their work became easier. It applied two types of technologies which are Material Preservation Technology and Multifunction Technology.